The Analysis ANALISIS KEMAMPUAN MAHASISWA DALAM PROGRAM LATIHAN PROFESI (PLP) TERHADAP ASPEK KEPRIBADIAN, PEMBELAJARAN, MICRO TEACHING, DAN PENGEMBANGAN RPP: - - Sutirna -; Intisari - (Universitas Bengkulu, 2022)
The purpose of this study was to analyze the ability of students in implementing PLP in schools. This research method uses descriptive qualitative through a survey approach to directly pay attention to or observe students carrying out PLP activities, while the instruments used are standard assessments of personality, learning, lesson plans development, and micro teaching. The subjects of this study were PLP participants in the schools that were used as PLP locations. The results of the assessment analysis conducted by the civil servant teachers and PLP assistant lecturers found that the level of personality, learning, RPP development and micro teaching aspects of PLP participants was included in the very good category.